Cajal Cell Counts are Important Predictors of Outcomes in Drug Refractory Gastroparesis Patients With Neurostimulation. Issue 5 (May 2019) - Omer, Endashaw; Kedar, Archana; Nagarajarao, Harsha S.; Nikitina, Yana; Vedanarayanan, Vetta; Subramony, Charu; Lahr, Christopher J.; Abell, Thomas L.
Abstract : Background and Aims: Cajal cells serve as the pacemaker cells of the gastrointestinal tract and regulates peristalsis. On the baisis of that fact, it has been hypothesized that a decrease in Cajal cells can lead to gastroparesis and other motility issues. Treatment with medications has a limited efficacy and most resort to gastric electrical stimulation (GES) devices for symptomatic relief. We believe that the number of Cajal cells present is directly proportional to symptomatic relief with GES. Materials and Methods: Twenty-three (white female) subjects were recruited from the gastric motility clinic University of Mississipi for this study with the criteria of drug refractory gastropersis. Symptoms were measured using Likert scale and gastric emptying times were measured pre-GES and post-GES. Serosal electrogram measurements were recorded during surgical placement of permanent electrical stimulator under various modes. Cajal cell count scoring via immunohistochemistry were performed during the implantaion of the GES. Results: The data were grouped in 2 categories based on the Cajal cells that is ≥2.00 and <2.00. Subjects with higher Cajal cells reported a statiscially improvement in gastroperesis symptoms. Significant differences were also noted in the first hour gastric emptying study. The mean group difference is 17.5 (95% confidence interval, 1.41-33.58; P =0.035). Serosal amplitude differences were noted being significantly higher in the group with ≥2 cajal cells. Conclusions: Electrograms obtained after GES demonstrates immediate improvement in gastric electrical activity and gastroparesis symptoms in patients with relatively higher Cajal cell counts when compared with patients with extensive loss of Cajal cells.